ANALYSIS OF THE LEGAL AND REGULATORY FRAMEWORKS OF MONEY LAUNDERING ACTIVITIES ON THE NIGERIAN ECONOMY - Oyaleke, Bukola (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
The impact of money laundering globally is overwhelming. It encourages illicit financial flow. Governments across the universe has responded to the waves by putting in place legal and regulatory frameworks to curb the menace. Notwithstanding the existence of legal and regulatory frameworks which are domestic and international in nature, the activities of money launderers are increasing on the daily basis. This paper therefore adopts doctrinal method of legal research attempts to examining money laundering in Nigeria vis-à-vis legal & regulatory impacts on the Nigerian economy. The paper asserts that non-existence of the relevant legal frameworks is not the bane of the fight against money laundering in Nigeria, but the problem of enforcement of the existing legal frameworks. The paper finds that the impacts of money laundering in Nigeria is multifaceted in nature. The paper recommends for full enforcement and implementation of the extant laws on the prevention and detection of the money laundering activities in Nigeria